Political institutions and trade-evidence for the long-run relationship and causality - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
We examine the long-run effects of the political institutional framework, measured by the political risk component of the International Country Risk Guide, on trade. Our results suggest that an improved political institutional framework is both a cause and a consequence of increased trading activity. However, we find no significant relationship in case of exporting activity for the high-income countries and the countries that possess better political institutions.
Keywords: F14; F55; 330; political institutions; trade; cointegration analysis